WHICH IS SUPERIOR? COMPARATIVE STUDY OF HIGH SCHOOL AND VOCATIONAL SCHOOL IN ACCOUNTING MAJOR - Shafira Zahra Wirawan; Syihab Rifqi Hadzami; Azzahra Nabila; Faza Auliana Zein; Nurfajrina Oktadiani (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Our research aims to determine and compare the influence of the school origin of students majoring in accounting on their understanding of accounting subjects when entering college. We used a qualitative research method with 3 methods of data collection, namely Zoom, voice recording, and direct interviews with 3 UPN